PROTEIN CHAIN INITIATION IN RABBIT RETICULOCYTES - Wilson, David B. (1970)
About 15% of the nascent α-chains isolated from in vivo labeled rabbit reticulocytes have methionine as their amino terminal amino acid. The methionine is predominantly on the shortest nascent chains, suggesting that methionine initiates the synthesis of rabbit hemoglobin and is rapidly removed during further synthesis.